Determination of antibiotic concentration in meconium and its association with fetal growth and development. (February 2019) - Zhao, Yingya; Zhou, Yuhan; Zhu, Qingyang; Xia, Bing; Ma, Wenjuan; Xiao, Xirong; Shi, Huijing; Zhang, Yunhui
Abstract: Background: The association between antibiotic use during pregnancy and neonatal birth outcomes has received considerable attention. Most of the previous assessment of antibiotic exposure during pregnancy relied on questionnaires and clinical prescriptions, and very few studies examined pregnancy exposure to antibiotics using human biomonitoring data. Objective: To explore the association between the cumulative exposure of antibiotics during the whole pregnancy and neonatal birth measurements using biomonitoring data of antibiotics in meconium. Methods: Three hundred and sixty nine pregnant women within the Maternal Psychological and Environmental Assessments of Kids Cohort Study were randomly selected into this study. Eighteen common antibiotics of six categories (six β‑lactams, three tetracyclines, four sulfonamides, one phenicols, one lincosamides and three fluoroquinolones) were selected as the target antibiotics in meconium. The measurement was conducted by ultraperformance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry platform. Neonatal birth measurements were obtained from the medical records. Multiple linear regression models were used to examine the associations of antibiotic exposure with neonatal birth outcome (birth weight, birth length) and placental growth indicators (placental surface area, placental weight). Logistic regressions were used to evaluate associations with small for gestational age (SGA) and large for gestational age (LGA). Results: Twelve of the eighteen antibiotics were found in 62.1% of the meconium, with detection rates ranging from 0.3% to 43.9%. The three antibiotics with the highest detection rates were chlortetracycline (43.9%), penicillin (16.5%) and chloramphenicol (10.8%), respectively. The highest antibiotic concentration among detected antibiotics was penicillin (24, 243.15 μg/kg). The concentration of penicillin was positively associated with the birth weight (β: 0.025; 95% CIs: 0.003–0.047). A significant positive association was also observed between the concentration of chlortetracycline and the placental surface area (β: 2.559; 95% CIs: 0.296–4.822). These associations were sex related and mainly observed in female newborns. Exposure to penicillin was also found to be associated with increased risk of LGA, which was consistent with changes in birth weight. Conclusions: Pregnancy exposure to certain antibiotics was associated with altered fetal growth and development, which may affect the normal growth trajectory of infants and children in later life. Highlights: Long-term exposure to low-dose antibiotics during pregnancy was very common. Exposure to penicillin during pregnancy was positively associated with neonatal birth weight. Elevated concentration of chlortetracycline was significantly associated with increased placental surface area. Penicillin was also found to be associated with increased risk of LGA, which was consistent with changes in birth weight. Prenatal cumulative exposure to low-dose antibiotics might interfere with fetal growth and development.